Marketing Strategy of Mixue Franchise in Bengkalis - Dwino Rani; Yunelly Asra (Politeknik Kampar, 2024)
This study aims to determine how the mixue franchise marketing strategy in Bengkalis. This research uses a qualitative descriptive method. The data collection techniques used are interviews and documentation. The object of this research is Mixue Bengkalis. The results of this study are the marketing strategy used by Mixue to market its products, namely market segmentation and marketing mix. The market segmentation used by Mixue Bengkalis is demographic segmentation because this segmentation describes consumer groupings based on generalizations, such as age, gender, religion, income and occupation. In the marketing mix strategy, mixue bengkalis determines the strategy in several ways, including the following: Product strategy mixue bengkalis adds the latest menu to meet market needs and innovates its menu, price strategy mixue bengkalis applies a national price strategy. The place strategy or mixue distribution channel can be reached offline, namely at the store's operational location and online through gobeng. The promotional strategy carried out by mixue bengkalis is to provide promos at certain events which are announced through mixue bengkalis social media accounts.